Effect of sonication time on physical and foaming properties of pasteurized milk - Siti Norazilah Maklin; Norliza Julmohammad; Suryani Saallah; Sariah Saalah; Nurul'azah Mohd Yaakub; Mohd Dona Sintang; Siti Norliayana Abd Rahman; Norziana Julmohamad (Elsevier B.V., 2025)
This study investigates the impact of ultrasonication duration on the properties of milk foam. Milk samples were subjected to ultrasonication for varying durations (1, 3, 5, 7, and 10 min), resulting in different sizes of native fat globules (249.5, 221.5, 222.6, 207.5, and 244.8 nm, respectively). The results indicate that viscosity increases as fat globule size decreases, with slight effect on zeta potential. NanoFoamer was identified as the optimal method providing the highest between foamability and stability (p < 0.05). Notably, foaming performance decreases after 7 min of sonication, highlighting the importance of selecting an appropriate frothing method to achieve the desired foam characteristics. Comparisons with non-ultrasonicated milk suggest that ultrasonication duration not only influences foamability by reducing fat globule size but also enhances foam stability through alterations in the fat globule sizes. Analysis of the foam structure revealed that smaller fat globules initially produce smaller, more numerous air bubbles with polyhedral shapes and well-defined lamellae. However, excessive reduction in fat globule size destabilizes the foam due to competitive protein adsorption and altered membrane composition, resulting in larger, less stable bubbles over time. Exploring ultrasonication times to enhances quality of milk and foam properties, offering significant benefits for dairy processing, product innovation and customer satisfaction.